Applying a 'glonacal' framework: the education choices of academically elite students in Singapore in relation to state scholarships. (27th May 2022) - Lu, Luke
ABSTRACT: This study is an attempt at better understanding the education choices of top-performing students in elite schooling. It applies a 'glonacal' framework (Maxwell 2018, "Changing Spaces – The Reshaping of (Elite) Education Through Internationalisation." In Elite Education and Internationalization: From the Early Years Into Higher Education, edited by C. Maxwell, U. Deppe, H. Kruger, and W. Helsper, 347–367. London: Palgrave Macmillan.) and focuses on the case of academically elite students who have graduated from an elite secondary school in Singapore, and their attitudes toward a scheme of undergraduate state scholarships. Drawing on life history interviews and focus group discussions with such individuals, I uncover how Singaporean informants portrayed aspirations of moving abroad for university education, and of returning to Singapore, commensurate with the state's strategy of tying them to the local through contractual bonds. Their characterisation of the scholarship in terms of 'comfort' and 'stability' must be contextualised within a nationalistic regime linking an elitist education system via scholarships to the local sphere of social and political power. The discussion serves to demonstrate relations between transnational mobility, the school and the local political economy, and how these have an influence on student subjectivities regarding education choices.